Investigation of Obtaining Natural Humic Acid From Asphaltites Commonly Found in Sirnak-Uludere Region - Taskesen, Edip; Acar, Sukru; Arli, Fatih; Dumrul, Hakan; Ertugrul, Gorkem; Bulbul, Saban; Ozcan, Emine (Gazi Univ, 2022)
The physical and chemical properties of asphaltites found in significant amounts in Sirnak and its surroundings are close to coal. But it differs from coal because of its formation sources and chemical processes. Asphaltites were separated from the oil in liquid state by tectonism and settled in other locations, hardened by chemical reactions during geological processes and turned into solid phase. Most of the heating need in the Southeastern Anatolia Region is met by asphaltites. However, it is a raw material with low calorific value, high content of ash, sulfur and moisture, and high potential to adversely affect air pollution.It contains nitrogen and humic acid that dissolves slowly in aqueous media and can be used as soil reinforcement. In this study, researches were made to obtain natural humic acid from the content of asphaltite samples taken from the mine reserve in Uludere district. In the experiments made with samples, the effects of pH changes, temperature changes, changes in mixing times, precipitation in KOH and HCl solution were investigated towards optimal humic acid recovery efficiency. Accordingly, natural humic acid was obtained with the highest efficiency of 33.95% as a result of the studies conducted with temperature experiments from the sample of the Uludere region.
Keywords: Asphaltite; humic acid; humate; dissolution; soil booster